Importance of Supplement Moringa Herbs (Moringa Oleifera) in Broiler Diet Under the Open System Farming: A Reviews: - - Wiyabot, Thunwa; P., Inphithak (Journal of Mahanakorn Veterinary Medicine, 2023)
Importance of supplement Moringa herbs (Moringa Oleifera) in broiler diet under the open system farming. The objectives of this study were to the Moringa (Moringa oleifera) is a robust, fast-growing herb that can be grown in any soil in tropical areas. Moringaceae are native to Asia. It is a medium-sized perennial Thai people prefer to plant around their houses. Moringa leaves contain a variety of phytochemicals, such as high levels of pro-vitamin A carotenoids and beta-carotene, (Pathum, 2009), and more importantly, β-sitosterol. The levels of fibre, calcium, phosphorus and total energy were 6.38%, 12.92%, 2.35%, 0.28% and 3,911 Kcal/kg of DM, respectively. (Dongjan, 2011). Moringa leaves contain a variety of important phytochemicals and can be applied for use in broiler feed to improve production performance. It was found that dried moringa leaves should be supplemented at 4-15 percent of the feed. As a result, the weight of the broiler and the quality of the carcass increased, and the amount of cholesterol in the blood decreased, so it is suitable for supplementing the feed of broilers.